2022
DOI: 10.18235/0004427
|View full text |Cite
|
Sign up to set email alerts
|

Options to achieve net-zero emissions from agriculture and land use changes in Latin America and the Caribbean

Abstract: Eleven countries in Latin America and the Caribbean have pledged to reach net-zero emissions by around 2050. Changes in the food system are key to reach these carbon neutrality goals, as agriculture and resulting land-use changes are responsible for almost half of greenhouse gas emissions in the region. We quantify the effect of supply-side (e.g., yield improvements, silvopasture, agroforestry) and demand-side (e.g., reduction of waste and losses, changing diets) options to reduce emissions and transform the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
3
9
0
1
Order By: Relevance
“…Other modelling studies have also shown the fundamental role of protection and restoration as cost‐effective strategies to reduce emissions in Brazil (De Oliveira Silva et al., 2018; Dumas et al., 2022; Gurgel et al., 2019; Köberle et al., 2020; La Rovere et al., 2018; Rochedo et al., 2018; Roe et al., 2019, 2021; Schaeffer et al., 2020), reinforcing our conclusions. It is urgent to enforce Brazil’s Forest Code and go beyond it.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other modelling studies have also shown the fundamental role of protection and restoration as cost‐effective strategies to reduce emissions in Brazil (De Oliveira Silva et al., 2018; Dumas et al., 2022; Gurgel et al., 2019; Köberle et al., 2020; La Rovere et al., 2018; Rochedo et al., 2018; Roe et al., 2019, 2021; Schaeffer et al., 2020), reinforcing our conclusions. It is urgent to enforce Brazil’s Forest Code and go beyond it.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has projected low‐emissions trajectories for Brazil, but these prior studies vary considerably in their scope (De Oliveira Silva et al., 2018; Dumas et al., 2022; Gurgel et al., 2019; Köberle et al., 2020; La Rovere et al., 2018; Rochedo et al., 2018; Roe et al., 2019, 2021; Schaeffer et al., 2020). While some confine their focus to specific mitigation measures or limited sectors and biomes (De Oliveira Silva et al., 2018; Dumas et al., 2022), others do not comprehensively assess specificities of national policies such as the FC across the interconnected sectors of LULUCF, agriculture and energy (Gurgel et al., 2019; Köberle et al., 2020; La Rovere et al., 2018; Rochedo et al., 2018; Schaeffer et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los impactos negativos, incluso, pueden incrementarse si no se detienen la deforestación y la degradación de suelos, las cuales se atribuyen en su mayoría a la expansión e intensificación de la agricultura y la ganadería (Castellanos y Lemos, 2022). En la región, los cambios en el uso de la tierra y los sistemas agroalimentarios son responsables de al menos la mitad de las emisiones totales de gases de efecto invernadero (Dumas et al, 2022).…”
Section: Oportunidades Y Desafíos De Los Sistemas Agroalimentarios En...unclassified
“…To this end, we combine two well-established and detailed models for the country (the regional economic partial equilibrium land use model GLOBIOM-Brazil [32,33], and the process-based, integrated assessment model BLUES [34]) to design locally meaningful policy scenarios (see Table 1 and Methods ) and project emissions from all sectors of the economy up to 2050. Other national-level modelling studies consider few dispositions of key national policies such as the Forest Code [35], specific sectors [36] or used global models and scenarios that are not validated against Brazilian official statistics for the historical period [4,37,38,39] (see Validation section in SI ).…”
mentioning
confidence: 99%